Incidence and survival of rare cancers in the US and Europe. (21st May 2020) - Botta, Laura; Gatta, Gemma; Trama, Annalisa; Bernasconi, Alice; Sharon, Elad; Capocaccia, Riccardo; Mariotto, Angela B.; ,
Abstract: Geographical variability of cancer burden was almost exclusively estimated for common cancers. Since rare cancers (RC) have become an area of priority for basic and clinical research and public health organizations, this paper provides, using a common methodology, a detailed comparison of incidence and survival for RC in the US and Europe. We estimated incidence and net survival of 199 malignant RC from data of 2 580 000 patients collected by 18 US‐SEER and 94 European registries, diagnosed within the most recent common period 2000‐2007. RC were defined according to the criterion of crude annual incidence rates <6/100 000. In total, 196 RC were classified as rare in both populations. Of these, 43 had incidence rates significantly different by at least 0.2 per 100 000:34 higher in the US and 9 higher in Europe. Five‐year net survival for all RC combined significantly differed: 54% in the US and 48% in Europe. Survival for 62 RC was significantly higher in the US vs 6 higher in Europe. Differences were not concentrated in a particular cancer family, and were mostly relevant for cases diagnosed >65+ years of age. Use of standardized methods evidenced that incidence and survival rate of majority of RC were higher in the United States compared to Europe. Possible reasons for such differences, requiring further studies, include distribution of risk factors, ability to diagnose RC, different registration practices, and use of updated International Classification of Diseases for Oncology. Abstract : Plot of crude incidence rates of rare and common cancers in Europe (y‐axis) vs the US (x‐axis) shows that most cancers were rare (crude incidence <6/100.000, low left square) in both population. Two cancers ( thyroid carcinoma and Diffuse B lymphoma ) classified as rare in the European population, however, were common in the US (low right square). In contrast, breast invasive lobular carcinoma was common in Europe and rare in the US (high left square).